2015
DOI: 10.1186/s10194-015-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the autonomic nervous system during paced breathing and mental stress in migraine patients

Abstract: BackgroundMigraine is a stress-related disorder, suggesting that there may be sympathetic hyperactivity in migraine patients. However, there are contradictory results concerning general sympathetic activation in migraine patients. To shed more light on the involvement of the autonomic nervous system (ANS) in migraine pathophysiology, we investigated cardiac and cardiovascular reactions during vagal (paced breathing) and sympathetic activation (mental stress test).MethodsHeart rate variability parameters and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Another study based on analysis of the electrocardiogram during sleep described reduced parasympathetic activity with sympathetic predominance [131]. In our own study we saw an exaggerated parasympathetic response to the pupillary reflex after a strong vegetative stimulus (cold water) [132] and a tendency to less parasympathetic and simultaneously more sympathetic activation in the control of the heart rate after mental stress or paced breathing [133]. One possible explanation for these different findings may be that there is a differential effect of migraine on the autonomic control of cranial autonomic reflexes and the cardiovascular system.…”
Section: Discussionmentioning
confidence: 80%
“…Another study based on analysis of the electrocardiogram during sleep described reduced parasympathetic activity with sympathetic predominance [131]. In our own study we saw an exaggerated parasympathetic response to the pupillary reflex after a strong vegetative stimulus (cold water) [132] and a tendency to less parasympathetic and simultaneously more sympathetic activation in the control of the heart rate after mental stress or paced breathing [133]. One possible explanation for these different findings may be that there is a differential effect of migraine on the autonomic control of cranial autonomic reflexes and the cardiovascular system.…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, similar to our results, some studies revealed no difference in migraine. Researchers evaluated the autonomic system function by using HRV and skin conductance responses in EM and controls; no significant differences were found ( 28 ). Researchers used vertical tilt test, Valsalva maneuver, grip test, cold-stress vasoconstriction, BP variability, and arterial baroreflex to examine the autonomic regulation in episodic and chronic forms of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…These stress responses can be observed, for example, after application of air-jet (2), painful stimuli (130), and also when the animal is placed in a novel and/or noisy environment (73). Similar cardiovascular and respiratory stress responses are observed in humans after application of combined physical and evaluative stressors (18), during mental stress (123), or in response to racially noxious images (28) or fearful faces (46) Various hypothalamic areas were originally defined as hypothalamic defense areas (HDA) because electrical or chemical stimulation of these regions produced characteristic behavioral and physiological defense responses (34,39,49,62,106). Other key regions involved in the defense reaction were subsequently described, such as the PAG (7,24).…”
Section: Defense Reactionmentioning
confidence: 86%